The Role of Multimedia in Developing Civic Education - Rosmiati, Yatti; Akhirudin, Akhirudin; Sugianto, Sugianto; Mulyana, Ahmad Nana Mahmur; Rustandi, Roni (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
The development of engaged and accountable citizens is greatly aided by civic education. Multimedia is a powerful tool for communicating civic ideas in the digital age. According to research, multimedia can enhance students' comprehension through engaging visuals, high levels of involvement, and convenient accessibility. Multimedia integration in the curriculum can boost learning efficacy and promote student engagement. Multimedia serves as both a tool and a guide for technology-based learning. There are still issues, though, like kids' unequal digital abilities and restricted access to technology. Support and a fair allocation of resources are therefore required to ensure that every student can make the most of multimedia. Multimedia use is still a viable creative way to raise the standard of civic education, even when a lack of resources is a barrier. Strategies for deploying multimedia more successfully and inclusively require greater investigation